2019
DOI: 10.1038/s41598-019-45944-z
|View full text |Cite
|
Sign up to set email alerts
|

On the Elevated Temperature Thermal Stability of Nanoscale Mn-Ni-Si Precipitates Formed at Lower Temperature in Highly Irradiated Reactor Pressure Vessel Steels

Abstract: Atom probe tomography (APT) and scanning transmission electron microscopy (STEM) techniques were used to probe the long-time thermal stability of nm-scale Mn-Ni-Si precipitates (MNSPs) formed in intermediate and high Ni reactor pressure vessel steels under high fluence neutron irradiation at ≈320 °C. Post irradiation annealing (PIA) at 425 °C for up to 57 weeks was used to determine if the MNSPs are: (a) non-equilibrium solute clusters formed and sustained by radiation induced segregation (RIS); or, (b) equili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…While, the APT MNSP statistics were limited, scanning transmission electron microscopy-energy dispersive X-ray spectroscopy (STEM-EDS) characterization confirmed the stability of the larger MNSPs. These results are consistent with cluster dynamics and kinetic lattice Monte Carlo models [16,32], which predict a large reduction in precipitate number density (N) at small r < rc at the high PIA temperature of 425°C, in a solute depleted matrix. Thus to further explore the thermal stability of MNSPs, we designed and carried out a special heavy ion irradiation experiment for the same Cu free high Ni steel.…”
supporting
confidence: 86%
See 4 more Smart Citations
“…While, the APT MNSP statistics were limited, scanning transmission electron microscopy-energy dispersive X-ray spectroscopy (STEM-EDS) characterization confirmed the stability of the larger MNSPs. These results are consistent with cluster dynamics and kinetic lattice Monte Carlo models [16,32], which predict a large reduction in precipitate number density (N) at small r < rc at the high PIA temperature of 425°C, in a solute depleted matrix. Thus to further explore the thermal stability of MNSPs, we designed and carried out a special heavy ion irradiation experiment for the same Cu free high Ni steel.…”
supporting
confidence: 86%
“…The previous PIA study of neutron irradiated CM6 showed that MNSPs below rc ≈ 2.2 nm redissolved in much shorter times at 425°C, assuring that the 52 week PIA results will not be affected by kinetics [16]. Standard FIB liftouts (see SI) were extracted and fabricated into APT tips and TEM foils at a depth of ≈ 400-600 nm from the surface, where the damage profile is relatively flat.…”
mentioning
confidence: 93%
See 3 more Smart Citations